Emotional Intelligence and Personality Traits in Higher Education - Salceanu, Claudia; Agapie, Oana-Maria (Technium Social Sciences Journal, 2022)
Emotional intelligence is a field that has been studied repeatedly lately due to the success achieved by Goleman’s works, which introduced several personality traits to the definition of emotional intelligence. According to researchers the investigation of emotional intelligence in combination with personality traits represents the possibility of improving social relations and educational environments. A sample of 100 students from universities in Constanta and Bucharest was assessed with the Five Factor Personality Inventory (from Cognitrom Assessment System) and with Mihaela Roco’s Emotional Intelligence Survey. We presumed the existence of correlations between emotional intelligence and extraversion, autonomy, kindness, conscientiousness, and emotional stability. We obtained significant correlations only for the first two variables, although studies in the scientific literature have discovered positive relationships between all of them. Results are discussed in the context of the importance of emotional intelligence for human life.